Elimination administrative barriers as a form of optimization of investment and business climate in the country (on the example of Italy) - B. R. Shakirtkhanov (Путеводитель предпринимателя, 2020)
The main contribution to formation of favorable investment climate is made by such factors, as lack of administrative barriers and the corruption mechanisms which have been built in infrastructure of development of business. The suspense of these problems creates a high field of uncertainty and risks for business especially within long-term projects. Essential element of favorable investment climate - is degree of satisfaction with quality of the state services.